Implementation Standards Access to Hospitals and Continuity Of Service - Dwi Yuliannisa Amri; Nur Hidayah; Ekorini Listiowati (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2019)
Access to a hospital and continuity of services are very important for the continuity of the hospital so that people who need health services are interested in visiting the hospital and utilizing the health services. The aims of the research are to find out the implementation of access to the hospital and continuity of service at X Hospital. The design of the research was descriptive qualitative research with observation and interview to collect the data. In observation, the subjects are 180 patients registered. In the interview, step is human resources who concerned on hospital access and continuity of service. Data analysis used interviews coding and calculated the observation result. Results and discussion are Observations on the implementation of a standard operating procedure for hospital access and continuity of services have been carried out in excess of 80%, but there are obstacles in the implementation, one of which is not all clinical staffs know the step in standard operational procedure. The conclusion is Clinical staff has implemented the standard operational procedure of Hospital access and service continuity exceeds 80%.